INTRODUKSI TEKNOLOGI PENGOLAHAN DAUN KELOR YANG MENDUKUNG EKONOMI MASYARAKAT DI POSDAYA BERINGIN SAKTI - Zasmeli Suhaemi; Wartis Anwar; Titi Sumarni; Mahyudi Irgantoro; Yusniati Yusniati (LPPM Universitas Andalas, 2018)
Koto Baru Village Sub-District Lubuk Begalung is one of area in Padang City, West Sumatera. Moringa plants (Moringa Oleifera) are very easy to grow and do not need special qualifications land and are an annual nature, so it does not burden the society in its management. Moringa products could be a business opportunities of herbal medicine field such as Moringa tea, and Moringa noodle. Such business could invite the society to manage Moringa plants that the result could be sold and consume by them, to get healthy life and more income. In order to giving more knowledge about Moringa tree and management to society, the steps are: 1) Socialization, 2) Training, and 3) Associating. Based on those activities, it conclude that society respond to something new and beneficial for life are high. It is proven by the enthusiasm of community . One of Moringa products are Merungai tea and Moringa noodle. Nowadays, the society had sell Moringa tea Rp. 10,000,- per 25gr packages that produce by one three of Moringa. The calculation result on development and management 40 trees could reach up to Rp. 1,000,000,- income per month in minimal number.